Noun Phrases in Czech Their Structure and Agreements - Veselovská, Ludmila (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
The study presents a systematic and complete morpho-syntactic analysis of Czech nominal phrases in a generative framework, based on universal structures and morpho-syntactic principles. The author cites relevant studies in the field, assuming that morphology results from steps in syntactic derivations that reflect the underlying structure (Radically Distributed Morphology). Theoretical claims are based on examples (including corpus data) and contrasted paradigms. Most data come from Czech, but other languages are also used to demonstrate more universal characteristics of the phenomena. The paradigms cover (i) the structure and feature content of nominal projections including adjectives, possessives and quantifiers, and (ii) agreements with nominal constituents such as pronominals and coordinates.
Keywords: jmenné fráze; čeština; mluvnice; noun phrase; Czech language; grammar; elektronické knihy; electronic books